Effect of technological parameters on mechanical properties and microstructure of heat-assisted friction stir welded joints of 6061 aluminum alloy - Hoang-Linh Nguyen; Van-Trung Pham; Duc-Binh Luu; Thien-Phuc Tran (PLoS ONE, 2025)
This study investigates the influence of key technological parameters on the mechanical characteristics and microstructure of heat-assisted friction stir welded (FSW) joints of AA6061 aluminum alloy pipes. Specifically, the effect of tool rotation speed, transverse speed, and tool shoulder diameter was evaluated. An experimental campaign was conducted using a three-level, three-factor composite design, with the primary objective of determining the optimal combination of these parameters to maximize the tensile strength of the weldments. AA6061 aluminum alloy pipes, with a thickness of 5 mm and an outer diameter of 80 mm, were joined using a resistance preheating FSW (RPFSW) process. The input parameters were varied at three distinct levels: rotation speed (1250, 1500, 1750 rpm), transverse speed (75, 87.5, 100 mm/min), and shoulder diameter (12, 15, 18 mm). Tensile tests were conducted to evaluate mechanical strength, and optical microscopy together with scanning electron microscopy (SEM), was employed to examine the microstructure of the weldments. The results indicate that the weldments achieved a tensile strength ranging from 49.7% to 72.4% of the base material. The optimal processing parameters were identified to achieve the highest predicted tensile strength of 198.15 MPa, corresponding to a transverse speed of 100 mm/min, a rotation speed of 1629 rpm, and a shoulder diameter of 13 mm. Microstructural analysis revealed that appropriate RPFSW parameters lead to suitable temperature and material flow, which in turn reduces weld defects and enhances the overall mechanical properties of the joint.